Integrating Sipakatau Local Wisdom into Interactive Digital Comics to Enhance Civic Learning and Character Development in Elementary Schools - Ratna Rendi; Abdul Kadir; Harmita Sari (AL-ISHLAH: Jurnal Pendidikan, 2026)
Civic education in elementary schools is essential for developing students’ civic understanding and character; however, instruction often remains text-based and insufficiently connected to learners’ cultural contexts. This study investigates the effectiveness of integrating Sipakatau local wisdom into interactive digital comics as a culturally responsive instructional medium.A quantitative quasi-experimental design with a non-equivalent control group pretest–posttest model was employed. The sample comprised 19 sixth-grade students from an Indonesian elementary school. Data were collected from a civic learning outcomes test and a character values questionnaire. Analyses included descriptive statistics, assumption testing, paired-sample t-tests, and effect size calculation.The intervention produced a statistically significant improvement in civic learning outcomes, with mean scores increasing from 57.00 to 77.53 (p 0.05). The effect size was large (Cohen’s d = 1.65), indicating substantial practical impact. Gain analysis revealed that 84.2% of students achieved moderate to high improvement, demonstrating consistent learning enhancement across participants.Embedding Sipakatau values within interactive digital narratives appears to enhance student engagement and deepen conceptual understanding of civic content. The culturally grounded approach supports meaningful learning by connecting abstract civic principles with students’ lived experiences.Interactive digital comics incorporating local wisdom represent an effective and practical pedagogical strategy for strengthening elementary civic education and advancing culturally responsive digital learning practices.